Control of Mycobacterium avium subsp. paratuberculosis load within infected bovine monocyte-derived macrophages is associated with host genetics - Badia-Bringué, Gerard; Canive, María; Alonso-Hearn, Marta (Frontiers in Immunology, 2023)
The genetic loci influencing individual resistance to Mycobacterium avium subsp. paratuberculosis (MAP) infection are still largely unknown. In the current study, we searched for genetic loci associated with resistance to MAP infection by evaluating the performance of monocyte-derived macrophages (MDMs) isolated from the peripheral blood of 75 healthy Holsteins cows and infected ex vivo with MAP. Bacterial load (log colony-forming units, log CFUs) within MDMs was quantified at 2 h and 7 days p. i. using a Bactec MGIT 960 instrument. In addition, the expression levels of some genes with important roles in the innate immune response including epiregulin (EREG), complement component C3 (C3), galectin-9 (Gal9), and nitric oxide (NO-) were measured in the supernatant of the infected cells. DNA from peripheral blood samples of the animals included in the study was isolated and genotyped with the EuroG MD bead Chip (44,779 single nucleotide-polymorphisms, SNPs). Linear mixed models were used to calculate the heritability (h2) estimates for each indicator of MDM performance, MAP load within MDMs and EREG, C3, Gal9, and NO-expression. After performing a genome-wide association study, the only phenotypes that showed SNPs with a significant association were the bacterial load within MDMs at 2 h (h2 = 0. 87) and 7 days (h2 = 0.83) p.i. A total of 6 SNPs, 5 candidate genes, and one microRNA on the Bos taurus chromosomes BTA2, BTA17, BTA18, and BTA21 were associated with MAP load at 2 h p.i. Overlap was seen in two SNPs associated with the log CFUs at 2 h and 7 d p.i. The identified SNPs had negative regression coefficients, and were, therefore, associated with a low bacterial load within MDMs. Some of the identified SNPs were located within QTLs previously associated with longevity, reproductive, and udder health traits. Some of the identified candidate genes; Oxysterol Binding Protein like Serine Rich Nuclear Protein 3, and the Coiled-Coil Domain Containing 92 regulate cellular cholesterol trafficking and efflux, apoptosis, and interferon production, respectively. Taken together, our results define a heritable and distinct immunogenetic profile in MAP-infected macrophages designed to limit bacterial load early after infection.